Children’s Perceived Ease of Use of a Projected Augmented Reality Game Designed for Balance and Coordination Training - Yishi Liu; Leigh Achterbosch; Grant Meredith; Evan Dekker; Suryani Lim; Andrew P. Lavender (Technologies)
Developing balance and coordination skills is essential for children, especially those aged 4–8, but limited Health and Physical Education (HPE) programs in schools hinder effective training. Game-based learning and Augmented Reality (AR) technologies offer promising ways to enhance these skills by providing immersive HPE experiences. An AR exercise-game prototype was developed to train children’s balance and coordination, with 19 children aged 4 to 9 testing the prototype. Post-activity surveys revealed high engagement and interactivity ratings. The difficultly of the current prototype was found to be appropriately challenging for 4- to 6-year-olds. Feedback emphasized a preference for interactive, challenging elements, suggesting improvements in difficulty customization, visuals, and technical stability. Competitive play between multiple children testing the prototype encouraged repeated attempts, but also highlighted the need for improved tracking solutions and lab setup. Overall, the innovative design shows educational potential but requires further large-scale testing on a refined version to assess its effectiveness in balance and coordination training.